2021
DOI: 10.3390/merits1010007
|View full text |Cite
|
Sign up to set email alerts
|

Career Networks in Shock: An Agenda for in-COVID/Post-COVID Career-Related Social Capital

Abstract: The COVID-19 pandemic was a career shock for many, including early and mid-career researchers. Due to the (digital) transformation it has caused in the social domain, it may have lastingly changed the rules for career development. In this conceptual paper, we investigate how the changed social environment created gaps in our understanding of academic career development and the role social capital plays in it. Our narrative review of the literature arrives at three major gaps: two are related to the nature, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Still, we consider it a meaningful pathway for the future to collect data that is more sensible to the details of this subject. A more fine-grained scale, or a relational approach such as social network analysis ( Froehlich, 2021 ), may be useful tools that allow for more detailed implications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Still, we consider it a meaningful pathway for the future to collect data that is more sensible to the details of this subject. A more fine-grained scale, or a relational approach such as social network analysis ( Froehlich, 2021 ), may be useful tools that allow for more detailed implications.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpected situations such as COVID-19 aggravated the challenges with which (novice) teachers are confronted under normal circumstances; studies report increased stress and a higher propensity for depression and burnout ( Anderson et al, 2021 ; Pressley, 2021 ; Santamaría et al, 2021 ). Importantly, these new demands also need to be seen in the context of generally increased stress levels due to the pandemic itself—for example, through health issues in family or oneself, or caretaking responsibilities ( Froehlich, 2021 )—and the probability of increasing them even more ( Bakker et al, 2005 ; Bakker and Demerouti, 2007 ). Also in the Austrian context, a recent study showed that the additional workload and the lack of digital skills are a great burden for teachers ( Woltran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations